Empowerment issues in Japan’s care industry: Narratives of Filipino nurses and care workers under the Economic Partnership Agreement (EPA) labour scheme - Vilog, Ron Bridget T. (Animo Repository, 2020)
Japan has been accepting foreign nurses and care workers through an Economic Partnership Agreement (EPA) with the Philippines, Indonesia and Vietnam. For more than ten years of its implementation, the EPA framework with the Philippines has confronted tremendous political hurdles from conservative politicians, groups and non-state agents which oppose the free trans-border flow of health workers. The lack of holistic state support has affected the implementation of the labour scheme under the Philippine-Japan Economic Partnership Agreement (PJEPA). In fact, majority of the nurses and care workers have failed the Japanese licensure examination, and an alarming percentage has decided to return to the Philippines after several years of training. Such trends indicate the failure of PJEPA to achieve a sustainable and mutually benefiting migration project. It is therefore imperative to examine the causes of this failure from the viewpoint of nursing and care delivery discourses. This paper contributes to the emerging literature that investigate EPAs and labour migration, with particular focus on the labour conditions and migrant decisions of individual care providers. Rethinking the concept of empowerment, we argue that the migration management regime, manifested in state’s healthcare policies and governance mechanism has been lacking meaningful support and guidance to the healthcare facilities, which translates to workers’ structural disempowerment. Nurses and care workers contest their dignity of labour, negotiate their experiences of deskilling, and seek strategies to survive the system. Disempowerment clearly impacts on individual migrant decisions, challenging established mechanisms and threatening the entire migration system to fail. © Penerbit Universiti Sains Malaysia, 2020.